Pengaruh Viral Marketing Melalui Aplikasi Instagram Terhadap Keputusan Pembelian - Sinta Rahayu Rahayu; Sinta Mak’ibah; Vicky F Sanjaya; Prima Rini Metri (Universitas Mitra Indonesia, 2022)
AbstractThis study aims to examine the effect of viral marketing through the Instagram application on purchasing decisions. A case study from this research is a student of Islamic business management at UIN Raden Intan Lampung Class of 2019. This research is a quantitative research. The method used in this research is a questionnaire. The sample of this study amounted to 36 respondents. Statistical tests were carried out using PLS-based Structurel Equation Modeling. The validity test uses the factor loading value, while the reliability test uses Cronbach's alpha, Composite Reliability and Avarage Variance Extracted (AVE) values. From the proposed hypothesis, it has a positive but not significant effect. The conclusion of this study is that viral marketing has a positive but not significant effect on purchasing decisions. Keywords: viral marketing, purchasing decisions